ANALISIS PENGARUH TINGKAT BAGI HASIL, INFLASI, DAN TINGKAT IMBALAN SBIS (SERTIFIKAT BANK INDONESIA SYARIAH) TERHADAP JUMLAH DEPOSITO MUDHARABAH PADA BANK UMUM SYARIAH DI INDONESIA PERIODE AGUSTUS 20 - Merli Nur Atiqah (IE 16 UMY 062, 2016)
This research aims to analyze the influences of the Ratio of Profit Sharing, Inflation, and Rate of Return SBIS (Sertifikat Bank Indonesia Syariah/Indonesian Bank Sharia’s Certificate) toward the Amount of Mudharabah Deposits in short-term or long-term. The object of this research was Sharia Bank (Bank Umum Syariah/BUS) in Indonesia overall by taking monthly data from August 2012 to June 2015. The research used samples as many as 35 data, which gotten from several agencies such as Indonesian Bank (Bank Indonesia/BI), Financial Services Authority (Otoritas Jasa Keuangan/OJK) and Central Bereau of Statistics (Badan Pusat Statistik/BPS). The analysis instrument of this res earch was analysis Error Correction Model (ECM) method. Based on the analysis, it can be concluded that the Ratio of Profit Sharing (Tingkat Bagi Hasil/TBH) has signficant influence and negative influence toward the amount of mudharabah deposits. Inflation gives positive and significant influence toward the amount of mudharabah deposits. While the rate of return SBIS does not give significant influence toward the amount of mudharabah deposits. Key Words: Ratio of Profit Sharing, Inflation, Rate of Return SBIS, and Mudharabah Deposits